2021
DOI: 10.1108/jgm-02-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Why we need to know more about diversity among the globally mobile: a systematic literature review of non-traditional expatriate research and future research agenda for minority expatriates

Abstract: PurposeThe purpose of this article is to provide a systematic literature review of research on non-traditional expatriates (NTEs) and an agenda for future research.Design/methodology/approachThe systematic literature review of NTEs 2010–2020 followed Moher et al.'s flow chart approach to undertaking a systematic literature review and included research on various categories of NTEs.FindingsThe article explains how the author developed an interest in NTEs and provides a brief distillation of the author's researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
(283 reference statements)
0
5
0
Order By: Relevance
“…The management of our working lives is, therefore, a topic that affects nearly all of us (and has spillover effects on others with whom we have non-work relationships) and thus has significant ramifications for society as a whole (Wilkinson, 2022: 1). The need to understand people management, including how to effectively manage an increasingly diverse and increasingly globally connected workforce (Hutchings, 2022), will become even more prevalent with some estimates suggesting that the current generation of workers may live until 100 and work until they are 70 (Gratton & Scott, 2016).…”
Section: Theory In/for Hrm Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of our working lives is, therefore, a topic that affects nearly all of us (and has spillover effects on others with whom we have non-work relationships) and thus has significant ramifications for society as a whole (Wilkinson, 2022: 1). The need to understand people management, including how to effectively manage an increasingly diverse and increasingly globally connected workforce (Hutchings, 2022), will become even more prevalent with some estimates suggesting that the current generation of workers may live until 100 and work until they are 70 (Gratton & Scott, 2016).…”
Section: Theory In/for Hrm Researchmentioning
confidence: 99%
“…Though phenomenon-driven HRM research has explored emerging phenomena in practice that did not have a tradition in academic research (e.g., talent management), theory-driven approaches are increasingly used to explain HRM and employment practices or offer alternative theoretical perspectives (Farndale et al, 2020). Further, along with HRM research being much more theoretically grounded than in earlier decades, recent literature reviews found the majority of refereed journal articles related to HRM include one theory, but some research is underpinned by two, three, or more theories (Cooke et al, 2019;Ererdi et al, 2022;Hutchings, 2022).…”
Section: Hrm and Theorymentioning
confidence: 99%
“…This research is not without its limitations. The studies included do not investigate different kinds of expatriates, such as flex-patriates, short-term assignees, international commuters, business travellers and non-traditional and minority expatriates (M€ akel€ a et al, 2017;Hutchings, 2021). Instead, it focuses only on OEs and SIEs, which we distinguish between (Table A2).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Traditional expatriates are described as white, male, middle-aged managers from Western sending countries, typically accompanied by a female spouse and children; by default, other expatriates might thus be classified as non-traditional (Guttormsen, 2018) suggesting that these latter individuals comprise “minorities” or “diversity” within an expatriate population. Although research into non-traditional expatriates is reported as limited (McNulty and Hutchings, 2016), particularly in respect of non-traditional family expatriation (Hutchings, 2021), it is important to note that we do not have definitive definitions of what constitutes traditional or non-traditional expatriates (Hutchings, 2021), how the intersectionality of diversity attributes might be categorised (for example, where might a single white male parent fit into a traditional or non-traditional/diverse expatriate classification) or indeed any idea of how many people are undertaking expatriation and the assignment types they are on (short-term, long-term, frequent flyer and so on) – be these organisationally assigned or self-initiated. This means that it is not possible to calculate the exact share of expatriate roles held by minorities.…”
Section: Literature Reviewmentioning
confidence: 99%